The Islamic Perspective on The Improvement of Family Economy in The New Normal - Budiman, Iskandar (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2021)
This paper concerns with how to build a balance of rights and obligations of husband and wife in fulfilling the economic needs of the family, especially in unusual circumstances. The paper aims to give an overall picture of the authority of the husband and wife regarding the domestic and public rights in the family, as well as to deal with the issue on family economy during the Covid-19 pandemic. The study of this paper used the explorative-qualitative research methods, with data obtained by disseminating questionnaires and studying documents related to the responsibilities carried out by the husband and wife. An initial investigation was conducted by taking into account the provisions stipulated in the formal legality of positive law. The data were then analyzed by utilizing a descriptive phenomenological approach through the interpretation of the data obtained from observation, interview, documentation, and literature review. The findings of this study indicate that men and women have equal rights. The concept of nature show that there is normative justification between husband and wife, stating that the domestic responsibilities are closely related to the shared rights and obligations that are balanced within the family and society, and that both husband and wife have the same rights in taking legal actions. In this new normal era, to strengthen the economically weak family in the community requires joint co-operation between the husband and wife so that they can meet the needs of the family and create a harmonious family.